Topological analysis and glass kinetics of Se-Te-Ag lone pair semiconductors. (28th September 2021) - El-Denglawey, A; Aly, K A; Sharma, Ekta; Arora, Rajeev; Sharda, Sunanda; Sharma, Pankaj; Dahshan, A
Abstract: The physical properties of Ag doped Se based ternary glassy alloys have been examined theoretically. ( Se 70 Te 30 )100 −x Ag x (0.0 ≤ x ≤ 8.0) chalcogenide alloys have been prepared by quenching method. The results show that the system is in floppy mode having constant average coordination number 2. The estimated density shows an increase with the Ag content. The mean bond energy and glass transition temperature vary in a similar fashion with an increment in Ag atomic % in the Se-Te system. The value of cohesive energy (1.91 eV mol −1 to 1.97 eV mol −1 ) and average bond strength (24.19 kcal mol −1 to 25 kcal mol −1 ) has shown increasing trend in the system. From the results of the investigated samples, the covalency parameter > 90%. So, it can be assumed that compositions are stable glass formers and may be used in the infrared system.